2021
DOI: 10.1093/plphys/kiab003
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose promotes stem branching through cytokinin

Abstract: Shoot branching is an important aspect of plant architecture because it substantially affects plant biology and agricultural performance. Sugars play an important role in the induction of shoot branching in several species, including potato (Solanum tuberosum L.). However, the mechanism by which sugars affect shoot branching remains mostly unknown. In the present study, we addressed this question using sugar-mediated induction of bud outgrowth in potato stems under etiolated conditions. Our results indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 87 publications
2
63
0
Order By: Relevance
“…The inhibitory effect of auxin on shoot branching is mediated by the antagonistic action of CK and SL (Rameau et al ., 2015; Barbier et al ., 2019b). Sugars have been reported to promote CK synthesis and accumulation in rose, potato stems and in arabidopsis shoots (Barbier et al ., 2015b; Kiba et al ., 2019; Salam et al ., 2021). Our results clearly demonstrated that gin2 is CK deficient and that the expression of CK‐related genes, including the CK synthesis gene IPT3 , were well correlated with HXK1 expression under different sugar availability conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibitory effect of auxin on shoot branching is mediated by the antagonistic action of CK and SL (Rameau et al ., 2015; Barbier et al ., 2019b). Sugars have been reported to promote CK synthesis and accumulation in rose, potato stems and in arabidopsis shoots (Barbier et al ., 2015b; Kiba et al ., 2019; Salam et al ., 2021). Our results clearly demonstrated that gin2 is CK deficient and that the expression of CK‐related genes, including the CK synthesis gene IPT3 , were well correlated with HXK1 expression under different sugar availability conditions.…”
Section: Discussionmentioning
confidence: 99%
“…We previously hypothesised that CK levels are important for promoting bud outgrowth when sugars are not readily available for buds (Barbier et al ., 2019b). Accordingly, CK has been reported to promote nutrient sink strength (Roitsch & Ehneß, 2000; Werner et al ., 2008; Peleg et al ., 2011; Wang et al ., 2016; reviewed in Fichtner et al ., 2021b), and it was recently reported that the sugar‐induced bud outgrowth in dark‐grown potato sprouts was mediated, at least partially, by a CK‐induced invertase activity (Salam et al ., 2021). In this view, we would expect that cytokinin synthesis mutants would indeed have a reduced response to decapitation, which enhances sucrose availability.…”
Section: Discussionmentioning
confidence: 99%
“…(2021) quantified the very early rosette bud growth that occurs after the floral transition but before bolting in long days, and observed less growth in plants with less photosynthetically active light. Recent advances in shoot branching research have illustrated that the release of bud dormancy and outgrowth into a new branch are dependent on sugar availability and involve sugar signalling pathways, notably mediated by trehalose 6-phosphate (Tre6P) and HEXOKINASE1, which interact with the hormones controlling branching (Mason et al, 2014; Barbier et al, 2015; Fichtner et al, 2017; Tarancón et al, 2017; Bertheloot et al, 2020; Barbier et al, 2021; Fichtner et al, 2021b; Salam et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Plants have developed different signalling pathways involved in sugar sensing, thus allowing plants to adjust their metabolism, growth and development to specific environmental conditions (Li and Sheen, 2016; Fichtner et al, 2021a). Some recent work has highlighted that sugar signalling pathways interact with auxin, strigolactone and cytokinin pathways to promote bud outgrowth (Barbier et al, 2015; Bertheloot et al, 2020; Fichtner et al, 2021b; Salam et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The interactions among sugars and hormones during the control of bud outgrowth are not yet fully resolved. Recent studies have indicated that sucrose can antagonise the effect of auxin by inhibiting SL perception to promote bud outgrowth (Bertheloot et al, 2020) and that the promotion of growth by cytokinins may only be effective under conditions where sugars are not readily available (Barbier et al, 2015b;Salam et al, 2021). Interactions between sugars and strigolactones have been recently highlighted in rice during the control of shoot architecture by the circadian clock (Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%